DEVELOPMENT OF A METHOD FOR A COMPREHENSIVE STUDY OF THE EFFICIENCY OF THE POWER SUPPLY SYSTEM OF INDUSTRIAL ENTERPRISES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
A method has been developed for a comprehensive assessment of the efficiency of the functioning of the power supply system of industrial enterprises based on the method of normalizing indicators. The structural scheme for calculating the coefficients characterizing the energy efficiency of the power supply system of industrial enterprises has been determined. The developed method makes it possible to study in detail the possibilities of the power supply system of industrial enterprises and identify additional resources for energy saving.